Adaptive bandwidth allocation algorithm based on the multi-threshold reservation mechanism - Geng CHEN; Wei-wei XIA; Lian-feng SHEN (Tongxin xuebao)
An adaptive bandwidth allocation algorithm based on multi-threshold reservation mechanism is proposed to guarantee the quality of service (QoS) of multi-services in heterogeneous wireless networks.With the bandwidth reserva-tion mechanism by setting multi-threshold in each network for every traffic,the adaptive bandwidth allocation scheme according to the transmission rate levels requirements for traffic k and the network status can be formulated as an optimal problem with the constraints of the bandwidth allocation matrix for each traffic and all users based on the multi-homing technology.A procedure of the iterative method is presented to solve the optimal problem of the formulated adaptive bandwidth allocation scheme.The optimized bandwidth allocation matrixes for traffics and for all users are obtained for the real-time network throughput maximization under bandwidth reserving thresholds and network capacity constrains and the bandwidth resource utilization efficiency of heterogeneous wireless network can be increased.Numerical simula-tion results show that the proposed algorithm can support QoS requiring transmission rate grades,decrease the new call blocking probability,increase the average user access rate and improve the network throughput of the heterogeneous wireless network by 40% to the largest extent.